Sinonasal Mass in the Setting of Prior Maxillofacial Surgery and Solid Organ Malignancy - Yihuai Qu; Jeffrey C. Mecham; Michael J. Marino (Sinusitis)
Fungal rhinosinusitis (FRS) can be classified into invasive and non-invasive forms, with the fungal ball (FB) representing a common non-invasive type with generally favorable outcomes post-operatively. The clinical presentation of FB can vary and be non-specific, and it is important to consider a wide differential diagnosis for sinonasal masses, including malignancy. We present the case of a 74-year-old female presenting with a two-year history of nasal obstruction and drainage. She has a history of breast cancer and prior maxillomandibular surgery, and imaging showed a poorly defined mass in the right maxillary sinus with possible hemorrhagic and/or proteinaceous content. Rigid nasal endoscopy revealed a friable mass, and endoscopic sinus surgery findings were consistent with FB. This case exemplifies the need to consider a broad set of differential diagnoses when evaluating sinonasal masses, especially if the patient has a prior malignancy or maxillomandibular surgical history, including FB and metastases to the paranasal sinuses. Given the presence of non-specific symptoms, it is important to consider early imaging for patients with distorted anatomy and a history of malignancy. Endoscopic sinus surgery, with high success rates, is the gold-standard treatment for FB.